Preface - Zaman H.B.; Robinson P.; Smeaton A.F.; De Oliveira R.L.; J?rgensen B.N.; Shih T.K.; Kadir R.A.; Mohamad U.H.; Ahmad M.N. (Springer Science and Business Media Deutschland GmbH, 2025)
[No abstract available]